Survey of thrips on eut flowers and neighbour plants and biology of Frankliniella panamensis Hood (Thysanoptera: Thripidae) - ZAPATA-C., ANGELA MARÍA; HINCAPIÉ - S., YOLIMA; MADRIGAL-C., ALEJANDRO (Revista Colombiana de Entomología, 1994)
A thrips populations survey on commercial cut flower crops and wild plants around the greenhouse was carried out in the locality of La Ceja, department of Antioquia. The following thrips species were found: Frankliniella panamensis Hood, Thrips australis Bagnall, Taeniothrips frici (Uzel), and Neohydotothrips near burungae (Hood) onchrysanthemum (Dendrantema grandiflora) and the species F. occidentalis (Pergande) on bouvardia (Beauvardia longiflorum). The species Haplothrips godwegi Franklin, Microcephalothrips abdominalis (D.L. Crawford), Psectrothrips interruptus, Frankliniella insularis (Franklin) and Frankliniella sp. on the following host plants: Tabebuia rosea flowers, Gazania sp.,Hemerocaluiz pava, Hypochoeris radicata, Trifolium repens, Physalis peruviana, Oxalis latifolia H.B.K., Cobaea scandens, Lantana moritziana, and Eucalyptus sp. The life cycle of F. panamensis was studied under laboratory conditions (T=24.8°C; R.H.=77.9%). The eggs, first instar larva, second instar larva, prepupa, and pupa lasted 2.5, 2.5, 5, 2.5, and 3 days, respectively. The average longevity of the adults was 47 days for the males and 61 for the females. Parthenogenic females laid an average of 17.79 fertile eggs/week and those which reproduce sexually 13.26 fertile eggs/week during their lifetime.